Women's Articulations of Aging: "Learning to Be Affected" Through Experiences in Recreational Ballet - Allison Jeffrey; Pirkko Markula; Corinne Story (Frontiers Media S.A., 2022)
In this article, we draw upon the experiences of mature recreational dancers who participated in classes facilitated by a professional ballet company and catered to older adults. Moving with 11 women through a 10-week ballet course, and immersing ourselves in the empirical material, we recognized opportunities for broadening our analysis of aging dancing bodies. Inspired by a Latourian understanding of bodies and a recent new materialist turn in humanities and social sciences, we became curious about the ways that the women were being affected by their experiences in ballet. The ballet studio, the barre, muscles, sweat, and music were all discussed as influential aspects contributing to their understandings of aging and dancing. Moving beyond biomedical prescriptions and extending socio-cultural constructions, we reveal opportunities for Latourian theory to dance with us toward re-imagining what is possible for aging recreational ballet dancers. Here, we allow the women's articulations of aging in ballet to exist as unique expressions unbound by limitations. Moving with women as they learn to become more affected through dance, we are given the opportunity to think about bodies, ballet and aging differently.